Challenges to the development of energy performance measurement : a systems thinking approach - Asikainen, Mikko (2016)
Growing global energy consumption and its consequent hindrance to sus-tainable development poses one of the greatest challenges of today. Impro-vement of the end-use energy efficiency is commonly regarded as one of the most basic and significant countermeasures for curbing the rising energy needs. However, it seems that the progress of end-use energy management is currently hindered due to the complexities involved in the measurement and management of energy efficiency. In essence, the lack of appropriate energy performance metrics constitute a gap between the current organizational needs and scientific literature. Furthermore, the current scientific debate has questioned whether ener-gy efficiency, as a current concept, is able to respond to the extant needs in business management. Thus, there exists a demand for a conceptual change that would enable organizations to simultaneously promote sustainable deve-lopment and reach concrete results from energy management. For this reason, this thesis focuses on the concept of energy performance, which is able to en-compass both operational and strategic dimensions of energy management. In order to address the above-mentioned research gap, this thesis explo-res the barriers that hinder the development of energy performance measu-rement in the context of industrial companies, government entities, wholesale and retail companies and real estate companies. As the barriers and their in-teractions seem to constitute a complex problem situation, the research prob-lem is approached from a systems thinking perspective, which enables the ho-listic examination of the barriers. The chosen approach departs from most previous research, which has typically studied barriers in isolation, neglecting the potential relationships between the barriers. The main achievement of this study is to introduce a model for unders-tanding the interactive nature of the barriers to the development of energy performance measurement. From the perspective of business management, the created model works as a tool for the management of change, as it inc-reases the understanding of the paradoxal problem situation and enables ra-tional discourse to take place. By doing so, the model aims to address the cur-rent needs of organizations in developing specific and quantitatively measu-rable performance indicators for energy.